Green coffee seed residue: A sustainable source of antioxidant compounds - Castro, A. C.C.M. [UNESP]; Oda, F. B. [UNESP]; Almeida-Cincotto, M. G.J. [UNESP]; Davanço, M. G. [UNESP]; Chiari-Andréo, B. G. [UNESP]; Cicarelli, R. M.B. [UNESP]; Peccinini, R. G. [UNESP]; Zocolo, G. J.; Ribeiro, P. R.V.; Corrêa, M. A. [UNESP]; Isaac, V. L.B. [UNESP]; Santos, A. G. [UNESP] (Elsevier, 2018)
Oil extraction from green coffee seeds generates residual mass that is discarded by agribusiness and has not been previously studied. Bioactive secondary metabolites in coffee include antioxidant phenolic compounds, such as chlorogenic acids. Coffee seeds also contain caffeine, a pharmaceutically important methylxanthine. Here, we report the chemical profile, antioxidant activity, and cytotoxicity of hydroethanolic extracts of green Coffea arabica L. seed residue. The extracts of the green seeds and the residue have similar chemical profiles, containing the phenolic compounds chlorogenic acid and caffeine. Five monoacyl and three diacyl esters of trans-cinnamic acids and quinic acid were identified by ultra-performance liquid chromatography/electrospray ionization-quadruple time of flight mass spectrometry. The residue extract showed antioxidant potential in DPPH, ABTS, and pyranine assays and low cytotoxicity. Thus, coffee oil residue has great potential for use as a raw material in dietary supplements, cosmetic and pharmaceutical products, or as a source of bioactive compounds.
Keywords: Agroindustrial residue; Antioxidant; Coffea arabica; Green seed residue; Secondary metabolites